2007
DOI: 10.1584/jpestics.r07-14
|View full text |Cite
|
Sign up to set email alerts
|

Earthworm biomarkers of pesticide contamination: Current status and perspectives

Abstract: Earthworms are standard test organisms in soil toxicity testing. They have been broadly used to assess environmental impact from heavy metal pollution; however, the knowledge on toxic effects from pesticides upon these organisms is still very limited. One of the ecotoxicological approaches to assess pollutant bioavailability and sublethal effects is the use of molecular and biochemical biomarkers. This review focuses on five issues that need further investigation: 1) field validation of earthworm biomarkers of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(15 citation statements)
references
References 97 publications
0
14
0
Order By: Relevance
“…The activity of these enzymes, as well as that of acetylcholine esterases, catalases and superoxide dismutases, has been investigated as useful biomarkers of exposure to contaminants such as pesticides, PAHs and heavy metals. 109,110) Biochemical approaches including fractionation of tissue homogenates, followed by chromatographic separation and spectrophotometric analyses are generally taken to investigate these enzymes; however, direct evidence as to the contribution of characterized enzyme(s) to pesticide metabolism has scarcely been reported. Recently, gene analysis using expressed sequence tags (EST; LumbriBase, http:// www.earthworms.org/) has been applied to earthworms.…”
Section: Relevant Enzymesmentioning
confidence: 99%
“…The activity of these enzymes, as well as that of acetylcholine esterases, catalases and superoxide dismutases, has been investigated as useful biomarkers of exposure to contaminants such as pesticides, PAHs and heavy metals. 109,110) Biochemical approaches including fractionation of tissue homogenates, followed by chromatographic separation and spectrophotometric analyses are generally taken to investigate these enzymes; however, direct evidence as to the contribution of characterized enzyme(s) to pesticide metabolism has scarcely been reported. Recently, gene analysis using expressed sequence tags (EST; LumbriBase, http:// www.earthworms.org/) has been applied to earthworms.…”
Section: Relevant Enzymesmentioning
confidence: 99%
“…Some authors (Aamodt et al, 2007;Rault et al, 2008;and Collange et al, 2010), have indicated that cholinesterase activity usually shows slow recovery rates until it reaches normal levels when exposed to organophosphates. This CbE activity in intestinal tissue of L. terrestris remains inhibited for a long period of time, more than 1-mo, after applying organophosphorus (González et al, 2010); that is, enzymatic activity is not recovered either by the spontaneous reactivation of the phosphorylated enzyme by the organophosphorus pesticide (Rodríguez-Castellanos and Sanchez-Hernandez, 2007) or the synthesis of the new enzyme during this inhibition period. This slow activity allows the stability of this response to organophosphorus pesticides and makes it a useful enzyme for biochemical assessment in monitoring exposure to agrochemicals.…”
Section: Discussionmentioning
confidence: 99%
“…They are considered useful tools in soil monitoring and assessment as an early warning of adverse ecological effects [52, 53]. This has increased the interest in the study of earthworm biological responses to pollutants.…”
Section: Discussionmentioning
confidence: 99%